Understanding Muslim patients: cross‐cultural dental hygiene care. Issue 2 (29th May 2012) - Sirois, ML; Darby, M; Tolle, S
<x xml:space="preserve">Abstract</x> To cite this article: Int J Dent Hygiene DOI: 10.1111/j.1601‐5037.2012.00559.x Sirois ML, Darby M, Tolle S. Understanding muslim patients: cross‐cultural dental hygiene care. Abstract: Background: Healthcare providers who understand the basic pillars of Islamic beliefs and common religious practices can apply these concepts, anticipate the needs of the Muslim patient and family, and attract Muslim patients to the practice. Objective: Cross cultural knowledge can motivate dental hygienists to adopt culturally acceptable behaviors, strengthen patient‐provider relationships and optimize therapeutic outcomes. Trends in Muslim population growth, Islamic history and beliefs, modesty practices, healthcare beliefs, contraception, childbearing, childrearing, pilgrimage, dietary practices, dental care considerations and communication are explained. Materials and methods: This paper reviews traditional Muslim beliefs and practices regarding lifestyle, customs, healthcare and religion as derived from the literature and study abroad experiences. Results and discussion: Recommendations are offered on how to blend western healthcare with Islamic practices when making introductions, appointments, eye contact, and selecting a practitioner. The significance of fasting and how dental hygiene care can invalidate the fast are also discussed. Conclusion: The ultimate goal is for practitioners to be culturally competent in providing care to Muslim patients, while keeping in mind that beliefs and practices can vary widely within a culture.